Korupsi Kemanusiaan: Antara Kebutuhan dan Keserakahan dalam Pengambilan Makanan Lebih oleh Kaum Dhuafa saat Mahasiswa Fisika 2022 Melakukan Kegiatan Pembagian Makan Sahur - Naelil Magfiroh; Elfani Zidni Ilma (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Humanitarian corruption has become an increasingly troubling issue in the context of social aid which is increasingly troubling in the context of social and humanitarian aid. This article examines humanitarian corruption activities through a case study of taking extra food by the poor when 2022 physics students carried out a meal distribution activity at dawn. The reasons behind this action are urgent needs and greed. This article also proposes solutions to prevent corruption and build a more just and empathetic society.